Fa’aliyatu Thariqah Make a Match fi Tarqiyati Maharati al-Qira’ah bi al-Lughah al-‘Arabiyyah: Tahlil Nataij at-Ta’allum: The Effectiveness of the Make a Match Method in Improving Arabic Reading Skills: An Analysis of Learning Outcomes - Neneng Roiyatul Muawanah; Dina Indriana; Ubaidillah (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2025)
Reading skills are fundamental to learning Arabic, as they play an essential role in understanding texts, developing vocabulary, and building other language competencies. However, the process of teaching reading in many schools still relies on traditional, teacher-centered methods, resulting in low student motivation and unsatisfactory learning outcomes. Based on these issues, this study aims to analyze the effectiveness of the “Make a Match” method in improving the reading skills learning outcomes of ninth-grade students at the Serang 2 Islamic Public Middle School. The uniqueness of this study lies in its focus on measuring the quantitative effect of the “Make a Match” method on reading skills learning outcomes, specifically, in the context of State Islamic Middle School 2 Serang, which has been limited in research. This study used a quantitative, pre-experimental design with a one-group, pre- and post-test. The study group consisted of ninth-grade students, while the study sample consisted of 30 ninth-grade (B) students. Data were collected using a cumulative test to measure reading learning outcomes, and the data were analyzed using a paired-samples t-test. The results of the study showed a statistically significant difference between the pre- and post-test scores, with a significance value of 0.000 (< 0.05). This study concluded that the Make a Match method. Keywords: Arabic, Cooperative Learning, Make a Match, Reading Skills.